Atuação dos doutores em contabilidade nos eixos ensino, pesquisa, extensão, produção técnica e gestão à luz da teoria do capital humano - Campos, Larissa Couto (2016)
According to Human Capital Theory, education is an activity predominantly of investment, once people acquire capabilities which offer future benefits, as assures Schultz (1960). These benefits can be economic, or non-economic, social and/or individual (ROBEYNS, 2006). In this sense, Cunha, Cornachione Jr. e Martins (2011) consider that the gain for society, originated from education, is superior to individual return rate, once the individual gain reverts, in a certain way, in some kind of advantage to society. In social scope, education\'s contribution can be analyzed through the preparation and education of future professors that will act in several learning areas. In this context, an observed investment in accounting scenario, refers to the increase in the number of graduation courses in Accounting Sciences and, since 1998, a rise in post-graduation programs in Accounting Sciences all over the country (MIRANDA et al 2013). For this reason, the study of the actuation of researchers and professors that contribute to Accounting Science development become relevant for the current conjuncture of accounting research, especially the doctors linked to post-graduation programs, which contribute directly to the education of new professionals besides the development of new researches. This way, the general objective of this study consisted of analyzing the evolution of post-graduation in accounting area and the actuation of Accounting Sciences doctors linked to these programs in the expansion period, by pillars of teaching, research, extension, technical production and management, in the light of human capital theory. In order to do so, a descriptive, documental and quantitative research was developed. For collected data treatment, descriptive statistics and Kruskal-Wallis non-parametric test were employed. The sample was compounded by 106 Accounting Sciences doctors whose degrees were acquired in Brazil and that act as tenured professors in Accounting Sciences post-graduation programs along the country. Collected data are derived from Lattes Curriculum and Research Directory of Accounting Sciences doctors, available on Lattes Platform. The collected information was separated by categories, according to education pillars, which are: teaching, research, extension, technical production and management. From the five analyzed pillars, there is a higher participation of doctors in the activities classified in the pillars of Teaching and Research, with emphasis to journals and congresses\' proceedings, Participation in events, ongoing Masters\' orientation and concluded monographs\' orientation. Whereas Extension pillar presented lower involvement of doctors of the sample, although it comprehends activities which near academy and society. In relation to the actuation of groups of doctors separated by the academic degrees\' time of acquisition, in the majority of the variables that stressed with higher participations, doctors titles obtained for longer time stood out in relation to the others. Whereas for doctors titles obtained for shorter time, between 2010 and 2014, it was checked production and participation in several activities, yet with lower intensity. This way, based on Human Capital Theory, it was noted that, in a whole, governmental and private investments on accounting education, especially in post-graduation, have been contributing to the development of accounting area teaching.